The passion for writing: A conversation with Mario Vargas Llosa - Rodriguez, Jorge (2022)
In the morning of December 18th 2002, what professor Jose Marfa Sese stated during a lecture, became a reality: "in order for a University to exist, classrooms are no needed, but a teacher, a student, a question in between, and a tree sheltering them both." This happened that day, in University of Piura's campus central gardens, where faculty and students gathered to chat with writer Mario Vargas Llosa. Former University President, Antonio Mabres, recalled the authors' first visit in 1981, when he said to be "a close witness of an affectionate welcome and support for those efforts our University was involved with." Twenty one years later, Vargas Llosa returned to lecture, for a couple of hours, on the passion for writing. Despite questions being many, and time scarce, everyone felt satisfied with the address. "Of all the universities I've known and visited around the world, I had never met one where the questions made to me purely concerned literature", the novelist remarked.